Modern Anticoagulant Therapy for Atrial Fibrillation: Patient Adherence in Clinical Practice - Yu. P. Skirdenko; N. A. Nikolaev; K. G. Pereverzeva; A. Yu. Timakova; A. S. Galus; S. S. Yakushin (Рациональная фармакотерапия в кардиологии)
Aim. To assess the adherence of doctors and patients to anticoagulant therapy for atrial fibrillation (AF).Materials and methods. An observational prospective study included 99 patients with AF at high risk of thromboembolic complications in Ryazan and Omsk. To study adherence, a questionnaire for quantitative assessment of treatment adherence ("QAA-25") was used. The questionnaire allows you to assess adherence by three main parameters separately: adherence to drug therapy, lifestyle modification and medical support. For the purposes of the study, adherence rates of less than 75% were regarded as insufficient, 75%. % or more as sufficient. To assess food preferences and determine the risk of changes in the activity of warfarin, a questionnaire of food preferences was used. The questionnaire allows you to assess the risk of alimentary increase (≥30 points) and decrease (≥60 points) of warfarin activity, as well as the overall risk of alimentary change (≥90 points) of warfarin activity in each patient, taking into account the volume and frequency of consumption of products that affect the activity of warfarin.Results. After the first visit, 99% of respondents received anticoagulant treatment. Rivaroxaban was the leader in prescribability among anticoagulants (36.7%). About a third of respondents were prescribed apixaban by a doctor (30.6%) and dabigatran  (17.3%)  and  warfarin  (19.4%)  were prescribed almost twice as rarely as rivaroxaban. Respondents with the highest rates of adherence to drug therapy, lifestyle modification and medical support are AF patients taking apixaban. The respondents who were prescribed rivaroxaban had the lowest level of adherence to drug therapy and lifestyle modification. And the lowest level of commitment to medical support is among respondents who have been prescribed warfarin. The number of people with a sufficient level of commitment did not reach half. Only 43.9% were ready to take prescribed medications and slightly more than a third (34.7%) agreed to come to appointments for a long time. But, despite the importance of lifestyle modification in patients with AF, only 16.3% of respondents said they were ready to give up bad habits, lose weight and lead a more active lifestyle. The proportion of people with sufficient adherence to drug therapy was the smallest in the group taking rivaroxaban (25.7%). The least number of respondents with sufficient commitment to medical support in the group taking dabigatran (25%). Only one in ten patients (11.1%) taking warfarin had a sufficient level of commitment to lifestyle modification. 15% of the study participants had an increased risk of alimentary changes in the activity of warfarin.Conclusion. Assessment of adherence to anticoagulant therapy by doctors in two regional centers (Omsk and Ryazan) showed high prescribability of preventive antithrombotic therapy, which corresponds to modern therapeutic approaches. At the same time, patients demonstrated rather low levels of adherence to drug therapy, lifestyle modification, and medical support.